Participatory Management Model for Youth Engagement in Sustainable Smallholder Oil Palm Practices - Delyana Rahmawany Pulungan; Dina Arfianti Saragih; Yulia Windi Tanjung; Tifany Zia Aznur (Fundamental and Applied Management Journal, 2026)
The sustainability of smallholder oil palm plantations depends not only on certification instruments and agronomic standards, but also on the capacity to regenerate farmers and involve younger actors in plantation governance. This study examines smallholder farmers’ understanding and perceptions of sustainable oil palm practices and develops a participatory management model for strengthening youth engagement in North Sumatra and Aceh, Indonesia. A quantitative field survey was conducted from May to September 2024 involving 384 independent smallholders participating in the People’s Palm Oil Rejuvenation Program in Langkat, Asahan, North Labuhan Batu, Nagan Raya, and Aceh Singkil. Data were analyzed using descriptive statistics and Structural Equation Modeling with AMOS. The findings show that respondents are dominated by older farmers, while youth participation remains structurally weak. Farmers’ understanding of sustainable oil palm practices is low, and their perception is only at a fair level. The barriers to adoption are not limited to technical knowledge, but also include weak farmer institutions, limited access to information, lack of certified seeds, insufficient capital, unclear economic incentives, and the negative social image of farming. The SEM results confirm six significant drivers of participatory management: initiation of participation, control, capacity to achieve goals, expert support, stakeholder support, and commitment. This study contributes a youth-oriented participatory management framework that explains how participatory mechanisms can transform sustainable palm oil standards into practical, institutionally supported, and economically meaningful actions for smallholders. The model provides practical guidance for government, cooperatives, palm oil companies, universities, and farmer groups in designing regeneration programs for young farmers.